Аналогії в американо-російському інформаційному протиборстві в роки «холодних війн» ХХ та ХХІ ст. - Беспека, В. Ю.; Bespeka, Vadym (Східноєвропейський національний університет імені Лесі Українки, 2017)
Проаналізовано основні способи інформаційного протиборства між США й Росією в різних сферах під час «холодних війн» 1945-1991 рр. та 2010 р. по сьогодні. Порівняно методи пропагандистського впливу на противника протиборчими сторонами. Окреслено основні риси роботи американських і російських органів пропаганди.The basic methods of the information opposing between the USA and Russia during «cold wars» 1945-1991 and 2010 - nowadays are analysed. Research was conducted by the method of comparative analysis and historical method. This allows through the prism of the second half of ХХ century «cold war» events to estimate propagandist manipulations of political strategists in the modern «cold» confrontation. At the same time, the study focused mainly on the issue of the propaganda activities of the above-mentioned countries in various fields.
The Analogies in the u. S-russian Information War During the Cold War Years of the XX and XXI Centurie
Keywords: пропаганда; «холодна війна»; санкції; локальні конфлікти; економічне протистояння; інформаційна війна; propaganda; cold war; sanctions; economic confrontation; the information war; local conflicts